Avaliação da atividade acaricida in vitro e in vivo de siloxanos organo-modificados em populações de Rhipicephalus microplus. - Marques, Camila Balconi (2018)
Currently, the Rhipicephalus microplus infestation causes great losses to cattle production in Brazil. The control of R. microplus is carried out almost exclusively using chemical products. In this way, the availability of products with acaricidal activity is limited and the development of new drugs is a slow and gradual process. It is known that the epidemiological conditions are more favorable to the maintenance of the tick in the environment as well as to the infestation of the animals. As a result, the animals have been treated more frequently, together with the excessive use of these acaricides, often without technical criteria or evaluation of the effectiveness of the treatments, culminating in the appearance of parasitic resistance by the tick. In this context, the present work aims to determine the acaricidal activity in vitro and in vivo of organo-modified siloxanes associated or not with Piperonyl Butotoxide (PBO). For this, R. microplus teleogines were collected from different properties in the state of Rio Grande do Sul, submitted to the immersion test of teleogines described by Drummond et al. (1973), also outlining a comparative efficacy with a commercially available combination of organophosphates and pyrethroids. After observing the in vitro results, in vivo tests were started at four properties in the Santa Maria - RS region. A medium concentration of the associated organo-modified siloxanes was applied by spraying bath and the efficacy evaluation was perfomed according to the proposed by Roulston et al. (1968). The results revealed high acaricidal activity (100%) in vitro in the concentration of 5% on non-associated form, and in combinations of concentrations of 0.6; 1.0; 2.5% with PBO. The in vivo results also increased with the association of PBO, being that the efficacy significantly improved. This work allowed to conclude that the organo-modified siloxanes demonstrated acaricide activity, in addition to the synergistic effect of PBO association. Evidencing its importance, in face of the current multiresistance scenario of the R. microplus tick to the different commercially available compounds.